Worries, Preparedness, and Perceived Impact of Covid-19 Pandemic on Nurses' Mental Health - Galletta, Maura; Piras, Ilenia; Finco, Gabriele; Meloni, Federico; D'Aloja, Ernesto; Contu, Paolo; Campagna, Marcello; Portoghese, Igor (Frontiers in Public Health, 2021)
Background: In times of global public health emergency, such as the COVID-19 pandemic, nurses stand at the front line, working in close contact with infected individuals. Being actively engaged in fighting against COVID-19 exposes nurses to a high risk of being infected but can also have a serious impact on their mental health, as they are faced with excessive workload and emotional burden in many front-line operating contexts. Purpose: The aim of the study is to analyze how risk factors such as perceived impact, preparedness to the pandemic, and worries were associated with mental health outcomes (crying, rumination and stress) in nurses. Methods: A cross-sectional study design was performed via an online questionnaire survey. Participants included 894 registered nurses from Italy. Participation was voluntary and anonymous. Multiple binary logistic regression was carried out to analyze the relationship between risk factors and health outcomes. Results: Increased job stress was related to higher levels of rumination about the pandemic (OR = 4.04, p < 0.001), job demand (OR = 2.00, p < 0.001), impact on job role (OR = 2.56, p < 0.001), watching coworkers crying at work (OR = 1.50, p < 0.05), non-work-related concerns (OR = 2.28, p < 0.001), and fear of getting infected (OR = 2.05, p < 0.001). Job stress (OR = 2.52, p < 0.01), rumination (OR = 2.28, p < 0.001), and watching colleagues crying (OR = 7.92, p < 0.001) were associated with crying at work. Rumination was associated with caring for patients who died of COVID-19 (OR = 1.54, p < 0.05), job demand (OR = 1.70, p < 0.01), watching colleagues crying (OR = 1.81, p < 0.001), non-work-related worries (OR = 1.57, p < 0.05), and fear of getting infected (OR = 2.02, p < 0.001). Conclusions: The psychological impact that this pandemic may cause in the medium/long term could be greater than the economical one. This is the main challenge that health organizations will have to face in the future. This study highlights that the perceived impact and worries about the pandemic affect nurses' mental health and can impact on their overall effectiveness during the pandemic. Measures to enhance nurses' protection and to lessen the risk of depressive symptoms and post-traumatic stress should be planned promptly.